Design of High Rate Blender Hydraulic Power Pack Unit on Stimulation Vessel – Study Case Stim Star Borneo for Offshore Operations at Delta Mahakam area – East Borneo - Hari Prastowo; Sutopo Purwono Fitri; Raja Oloan Saut Gurning; Sahrul Abidin (Institut Teknologi Sepuluh Nopember, 2017)
Application of Hydraulic Power technology in world industry today is still continue to increased. Not only in Industrial it’s self, but in Marine, Onshore and Offshore also use these technologies. Requirement of service in well services - Offshore Delta Mahakam region makes PT. Halliburton Indonesia as a Service Company increase his fleet service. The Type Stimulation Vessel Fleets - Stim Star Borneo is planned to improve the service unit of High Rate Water Pack (HRWP) with High Pressure Pump unit plus Gravel Pack Sand (GP) and High Rate Blender Unit. Blender High Rate is a unit tubular mixing blender driven by hydraulic power, motors blender, sand screw, pump suction and discharge pump that’s is installed unity. For that The authors will plan system, calculation and specifications of Hydraulic Power Pack Unit for High Rate the Blender. Calculations start from of Operasional Requirement Conditions, and continued with Design Block Diagram, P & ID, and also calculations of systems such as Head, RPM, Pipe Diamater, Pipe Thickness, Main Hydraulic Pump, Reservoir Tank and Cooler. Where The Requirement of Hydraulic Main Pump Power is 950 kW with Electric Motor as prime mover 950 kW. The final result of the design is show as Layout and Detail drawing in attachment.